Degradation of PsbO by the Deg Protease HhoA Is Thioredoxin Dependent - Roberts, Irma (2012)
The widely distributed members of the Deg/HtrA protease family play an important role in the proteolysis of misfolded and damaged proteins. Here we show that the Deg protease rHhoA is able to degrade PsbO, the extrinsic protein of the Photosystem II (PSII) oxygen-evolving complex in Synechocystis sp. PCC 6803 and in spinach. PsbO is known to be stable in its oxidized form, but after reduction by thioredoxin it became a substrate for recombinant HhoA (rHhoA). rHhoA cleaved reduced eukaryotic (specifically, spinach) PsbO at defined sites and created distinct PsbO fragments that were not further degraded. As for the corresponding prokaryotic substrate (reduced PsbO of Synechocystis sp. PCC 6803), no PsbO fragments were observed. Assembly to PSII protected PsbO from degradation. For Synechocystis sp. PCC 6803, our results show that HhoA, HhoB, and HtrA are localized in the periplasma and/or at the thylakoid membrane. In agreement with the idea that PsbO could be a physiological substrate for Deg proteases, part of the cellular fraction of the three Deg proteases of Synechocystis sp. PCC 6803 (HhoA, HhoB, and HtrA) was detected in the PSII-enriched membrane fraction.